Al3+‐Ion‐Triggered Conformational Isomerization of a Rhodamine B Derivative Evidenced by a Fluorescence Signal – A Crystallographic Proof. Issue 8 (9th February 2015) - Sen, Buddhadeb; Pal, Siddhartha; Banerjee, Samya; Lohar, Somenath; Chattopadhyay, Pabitra
Abstract: A newly designed rhodamine B anisaldehyde hydrazone exhibits Al 3+ ‐ion‐induced cis (L ) to trans (L′ ) conformational isomerization with respect to the xanthene moiety through a rotation about a N–N bond; the isomerization is indicated by a detectable naked‐eye color change and a turn‐on red fluorescence in 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES) buffer (EtOH/Water 1:9 v/v; pH 7.4) at 25 °C. In support of this observation, detailed spectroscopic and physicochemical studies along with density function theory (DFT) calculations have been performed. This cis ‐to‐ trans conformational isomerization is due to Al 3+ ion coordination, which induces this visual color change and the turn‐on fluorescence response. To strengthen our knowledge of the conformational isomerization, detailed structural characterizations of the cis and trans isomers in the solid state were performed by single‐crystal X‐ray diffraction. To the best of our knowledge, this is the first structural report of both cis and trans conformational isomers for this family of compounds. Moreover, this noncytotoxic probe could be used to image the accumulation of Al 3+ ions in HeLa and MCF‐7 cell lines. Abstract : A noncytotoxic rhodamine B anisaldehyde hydrazone exhibits an aluminium‐ion‐induced cis (L ) to trans (L′ ) conformational isomerization with respect to the xanthene moiety through a rotation about a N–N bond; the change is signaled by a red fluorescence response.